2020
DOI: 10.21474/ijar01/12108
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yoga Therapy on Frequency Domain Parameters of Heart Rate Variability in Prediabetics

Abstract: Introduction: Prediabetes is the budding stage of type 2 diabetic mellitus and imposes the elevated risk for cardiovascular diseases (CVDs) with significant morbidity and mortality. Non pharmacological strategies such as yoga therapy have marked impact in the mitigation of prediabetes. In this backdrop, the present study was conducted to study the effect of six months yoga intervention on heart rate variability in patients diagnosed with prediabetes. Further, it has been used as tool for the maintenance of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Another potential therapeutic use of HRV in the context of diabetes is HRV-based interventions to improve the regulation of glucose blood levels. For example, it was shown that HRV-based interventions, such as yoga or exercises which involve deep breathing, can improve HRV and glucose regulation in T2DM patients [ 48 , 49 , 50 ]. Integration of such interventions into diabetes treatment plans will enable a potential reduction in the risk for complications accompanying diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential therapeutic use of HRV in the context of diabetes is HRV-based interventions to improve the regulation of glucose blood levels. For example, it was shown that HRV-based interventions, such as yoga or exercises which involve deep breathing, can improve HRV and glucose regulation in T2DM patients [ 48 , 49 , 50 ]. Integration of such interventions into diabetes treatment plans will enable a potential reduction in the risk for complications accompanying diabetes.…”
Section: Discussionmentioning
confidence: 99%